2017
DOI: 10.1016/j.stemcr.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C and l-Proline Antagonistic Effects Capture Alternative States in the Pluripotency Continuum

Abstract: SummaryMetabolites and cofactors are emerging as key regulators of cell plasticity and reprogramming, and their role in the control of pluripotency is just being discovered. Here we provide unprecedented evidence that embryonic stem cell (ESC) pluripotency relies on the relative levels of two physiological metabolites, namely ascorbic acid (vitamin C, VitC) and l-proline (l-Pro), which affect global DNA methylation, transcriptional profile, and energy metabolism. Specifically, while a high VitC/l-Pro ratio dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 37 publications
5
68
2
Order By: Relevance
“…In addition to the role of ascorbate in reprogramming (84,85), a combination of ascorbate and retinol have been shown to enhance naive state acquisition by increasing TET expression and catalysis (99). In contrast, high ratios of L-proline to ascorbate prevents naive state maintenance, although the mechanism(s) by which L-proline induces epigenetic changes is yet to be elucidated (100). Collectively, these studies suggest a role for metabolism in influencing naïve versus primed pluripotency dynamics by facilitating chromatin remodeling through multiple specific metabolites.…”
Section: Metabolism and The Naïve Psc Epigenomementioning
confidence: 99%
“…In addition to the role of ascorbate in reprogramming (84,85), a combination of ascorbate and retinol have been shown to enhance naive state acquisition by increasing TET expression and catalysis (99). In contrast, high ratios of L-proline to ascorbate prevents naive state maintenance, although the mechanism(s) by which L-proline induces epigenetic changes is yet to be elucidated (100). Collectively, these studies suggest a role for metabolism in influencing naïve versus primed pluripotency dynamics by facilitating chromatin remodeling through multiple specific metabolites.…”
Section: Metabolism and The Naïve Psc Epigenomementioning
confidence: 99%
“…For example, the Jumanji C family of histone demethylases and the TET‐family enzymes, which catalyze the first step of DNA demethylation, require both the TCA cycle intermediate α‐ketoglutarate (α‐KG) and the reduced (Fe 2+ ) form of iron . Iron is more commonly in the Fe 3+ form but can be reduced to Fe 2+ by vitamin C, and several recent studies revealed the importance of vitamin C for promoting the activity of Jumonji C or TET‐family enzymes in ESCs , adult stem cells , and during iPSC reprogramming . Another important histone demethylase, lysine‐specific demethylase 1 (Lsd1), is also sensitive to metabolic changes as it relies on FAD as a cofactor .…”
Section: Metabolismmentioning
confidence: 99%
“…Vitamin C has emerged as a critical regulator of stem cell behaviors by enhancing somatic cell reprogramming, leading to a generation of induced pluripotent stem cells (iPSCs), by modulating the cellular epigenetic profile [8][9][10].…”
Section: Introductionmentioning
confidence: 99%